2022
DOI: 10.3390/agronomy12071712
|View full text |Cite
|
Sign up to set email alerts
|

Agroecological Screening of Copper Alternatives for the Conservation of Soil Health in Organic Olive Production

Abstract: The efficacy of soil conditioner (vermicompost tea), fertiliser (potassium silicate), and biological control agents (BCAs) as practical agroecological copper alternatives against olive leaf spot (Spilocaea oleaginea (Cast.) Hughe.) disease was investigated between 2018 and 2021 under organic management in a Mediterranean climate. In total, 9 agroecological alternatives to copper oxychloride (vermicompost tea, potassium silicate, Bacillus subtilis EU 007 WP, Platanus orientalis leaf extract, Mycorrhiza mix, sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A. Kir et al (2022), while studying the use of copper on olive plantations, concluded that copper accumulated not only in the soil layer, but also in the leaves and branches of trees, which negatively affected biodiversity and human health.…”
Section: Attributementioning
confidence: 99%
See 1 more Smart Citation
“…A. Kir et al (2022), while studying the use of copper on olive plantations, concluded that copper accumulated not only in the soil layer, but also in the leaves and branches of trees, which negatively affected biodiversity and human health.…”
Section: Attributementioning
confidence: 99%
“…A. Kir et al (2022) investigated the use of copper oxychloride against olive leaf spots and found that copper accumulated in the soil and in the fruits and leaves of olive trees, which posed a risk to human health. A.…”
Section: Introductionmentioning
confidence: 99%